Management of General Anesthesia in Difficult Airway: A Case Report - Taufiq Gemawan; Adelia Handoko; Muhammad Irsyad Amien; Nurrul Izza Misturiansyah; Muhamad Rizal Hadi Pratama (Journal of Agromedicine and Medical Sciences, 2023)
When dealing with clinical disorders known as difficult airways, airway management during general anesthesia still presents challenges. A cross-sectional study done in Indonesia in 2016 found that 28 out of 250 patients receiving general anesthesia had respiratory problems. The existing algorithm must be properly and effectively managed in order to resolve this issue. This case report discusses a 14-month-old pediatric patient with right preauricular lymphoma who will undergo tumor biopsy surgery using general anesthesia. The size of the tumor mass that has grown and covered the patient's airway makes it difficult to manage the airway during general anesthesia, making intubation impossible. To overcome this, bagging was carried out by improvising the technique of reversing the position of the mask cover on the patient during the operation. The patient can be saved and allowed to go home after treatment. Appropriate management during perioperative especially related to airway management will produce good results for patient health and safety. With this case report, hopefully it can add knowledge and an alternative ventilation technique if you encounter a similar case. Keywords: difficult airway, general anesthesia, lymphoma preauricular